A novel bandwidth enhancement technique for a compact right/left-handed (CRLH)transmission line (TL) based antenna - Wan Nordin, Mimi Aminah; Abd-El-Raouf, Hany Essam; Alam, A. H. M. Zahirul (2011)
A novel composite right/left-handed (CRLH) transmission line (TL) based metame- trial antenna with wide bandwidth is presented in this paper. The motivation behind the work was the increase in demand for compact metamaterial antennas for applications that require wide bandwidths [1]. Enhancement to the bandwidth of the antenna is achieved by incorporating two additional capacitances, in both, the shunt and series arm of the CRLH TL unit cell equivalent circuit. The additional capacitance in the series arm of the CRLH TL unit cell was added in parallel to the left-handed capacitance, CL, by which an increase in the total series capacitance is achieved. This was done by means of a cap in the form of the metal-insulator-metal (MIM), which was introduced on a layer below the radiating patches. The additional capacitance in the shunt arm of the CRLH TL unit cell was added in series to the right handed capacitance, CR, by which a decrease in the total shunt capacitance is achieved. This was done by means of a parallel plate that is being introduced on a layer between the vias and the ground plane of the unit cell. The proposed unit cell consists of the original mushroom structure (which is made up of a patch and a via connecting the patch to the ground plane), a cap and a parallel plate. Analysis of the dispersion characteristic of the proposed unit cell reveals a reduction in dispersion as compared to the unit cell without the two additional capacitances. This factor contributes to the increase in the bandwidth of the structure. The antenna con¯guration is in the form of a 2 £ 2 patch. A comparison made between the bandwidth of the proposed CRLH TL antennas with the conven- tional CRLH TL antenna, shows an increase in bandwidth from 9.2% to 18.5%. The proposed antenna is a tri-band and its length, width and height at the ¯rst resonant frequency are ¸0=26, ¸0=26 and ¸0=27, respectively; where, ¸0 is the free space wavelength.